2014
DOI: 10.1021/jp506640q
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization and Proton Transfer in the Forward and Reverse Photoswitching of the Fast-Switching M159T Mutant of the Dronpa Fluorescent Protein

Abstract: The fast-switching M159T mutant of the reversibly photoswitchable fluorescent protein Dronpa has an enhanced yield for the on-to-off reaction. The forward and reverse photoreactions proceed via cis-trans and trans-cis photoisomerization, yet protonation and deprotonation of the hydroxyphenyl oxygen of the chromophore is responsible for the majority of the resulting spectroscopic contrast. Ultrafast visible-pump, infrared-probe spectroscopy was used to detect the picosecond, nanosecond, as well as metastable mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 32 publications
(226 reference statements)
3
56
1
Order By: Relevance
“…Experimentally it was observed from time resolved UV–vis spectroscopy measurements that in dilute solution, the relative on‐to‐off photoswitching rate constant with continuous 473 nm illumination increased 65‐fold relative to the unmodified Dronpa samples, at pH 7.8 and 3 × 10 −6 M concentration, favoring monomeric forms . We further noted distinctly reduced on‐off phototransformation kinetics with increased protein concentration for both the wild type and mutant samples, in approximately the same concentration ranges.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Experimentally it was observed from time resolved UV–vis spectroscopy measurements that in dilute solution, the relative on‐to‐off photoswitching rate constant with continuous 473 nm illumination increased 65‐fold relative to the unmodified Dronpa samples, at pH 7.8 and 3 × 10 −6 M concentration, favoring monomeric forms . We further noted distinctly reduced on‐off phototransformation kinetics with increased protein concentration for both the wild type and mutant samples, in approximately the same concentration ranges.…”
Section: Resultssupporting
confidence: 51%
“…The small but reproducible cavity volume differences found in this study may therefore be in line with the significant rate enhancement. By comparing the isomerization rates in the monomer and the oligomeric states, we indeed found that the reactions occurs more efficiently in the monomer …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In the pH 4.3 structure,A sp25 is protonated on the outer Od2o xygen, whereas the OH group of darunavir hydrogen bonds with Asp25'.T herefore,anet two-proton transfer has occurred between the catalytic Asp residues and the OH group of the drug. This transfer was triggered by changes in the electrostatic properties of the protein resulting from the protonation of the four surface residues.T he electrostatic changes occur relatively far away (11)(12)(13)(14) from the catalytic site (Supporting Information, Figure S4). Thec atalytic site is not accessible to water when an inhibitor is bound, therefore we can deduce the proton transfer pathway.D1istransferred to the darunavir oxygen, while D2 shifts to Asp25.…”
Section: Chemiementioning
confidence: 99%
“…[8][9][10][11] Similarly, excited-state proton transfer has been studied in green fluorescent protein (GFP), mapping the pathway of the proton hopping from the fluorophore OH to a glutamate side chain through a water molecule and a serine residue. [12][13][14] However, in these examples the proton is transferred back to the OH group once the photoacids return to the ground state and regain their initial acidities.…”
mentioning
confidence: 99%